Tough Questions on Faith and Field Partnerships : A Commentary - Toop, Katie; Slimbach, Richard (Christian Relief, Development, and Advocacy: The Journal of the Accord Network, 2024)
The following is a response by Katie Toop (senior director of transformational development with World Concern) to the three questions Richard Slimbach poses on faith and field partnerships in his article “Asking Tough Questions About Transformational Development,” published in this journal in the summer of 2023 (Slimbach 2023). A follow up comment by Slimbach appears at the end. Both of these contributions were part of a webinar on June 27, 2023 discussing that article; the rest of the webinar content, consisting of two other responses and discussion around them, is published in this issue as well. The full recording of the webinar can be found at https://vimeo.com/844345288/e970fe8826?share=copy. The specific questions to which Katie Toop responds are: Does Danladi Musa (2012) accurately portray typical NGO-local church relations? How should Christian NGOs from the Global North relate to local churches in the Global South? What are the best ways to approach such partnerships? What are the major pitfalls? Why do many Christian congregations and development agencies tend to shy away from partnerships with non-Christian faith communities, non-sectarian grassroots NGOs, municipal government agencies, and non-violent protest movements? How accurately does James Davison Hunter diagnose the problem, and what implications might it have for the work of Christian NGOs? What missiological, theological, sociological principles (“theory of change”) are implicit within your organization’s external relationships (partnerships, networks, alliances, etc.)?